STANDARISASI PRODUK KEUANGAN SYARIAH TINGKAT NASIONAL DAN INTERNASIONAL - Hasbulloh, Achmad Shobirin; Dibaj, Muhammad Syarif; Rahmaniah, Amelia (Fakultas Syariah UIN Antasari, 2025)
This paper discusses the standardisation of Islamic financial products at the national and international levels to reveal what needs to be done to achieve standardisation of Islamic financial products at the national and international levels and how to ensure that Islamic financial products meet the established standards. This type of research is library research with a qualitative approach. Islamic financial products are products based on Islamic economic principles. Standardisation can be defined as the process of developing and implementing standards to ensure consistency, quality, and suitability of products. In the context of Islamic finance, the purpose of standardisation is to create a clear and transparent framework that can be followed by all Islamic industry players so that Islamic financial products and services are in line with Islamic principles, banking regulations, and market needs. According to the author, the way to achieve standardisation of Islamic financial products at the national and international levels is by establishing binding rules for all Islamic financial institutions that comply with Islamic principles, banking regulations, and market needs. To ensure that Islamic financial products meet Sharia standards and compliance, the Sharia Supervisory Board (SSB) must perform effectively. The author recommends that Muslims support Islamic financial institutions, even though in practice there are still some